Autonomy and Democratization of Islamic Education - Fekrat, Izzi; Sepriyanti, Nana; Kustati, Martin; Nurhasnah, Nurhasnah; Eldarifai, Eldarifai; Wahyuni, Sisri (International Journal of Educational Narratives, 2024)
Background. Autonomy is the freedom to maintain and promote the special interests of the region, with its own finances, determine its own laws, and self-government. Purpose. Educational autonomy according to the National Education System Law No. 20 of 2003 is revealed in the rights and obligations of citizens, parents, communities, and governments. Method. The research and development method is a research method used to produce certain products, and test the effectiveness of these products. Results. The results of this paper show that autonomy aims to autonomize a person or an institution or a region, so that educational autonomy has the aim of providing an autonomy in realizing the function of institutional education management. Conclusion. However, since the implementation of educational autonomy, it turns out that its implementation has not gone as expected, instead the implementation of autonomy has created many problems, namely the high cost of education. Meanwhile, the meaning of educational autonomy actually implies democracy and social justice, meaning that education is carried out in a democratic manner so that the expected goals can be realized and education is intended for the benefit of the community, in accordance with the ideals of the nation in educating the nation.